A Ukrainian Thinker? Hryhory Skovoroda - Koschmal, Walter (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The dissimilar similarity of Ukrainian and Russian cultures of the 18th century may be recognized in the theologians Feofan Prokopovich and Hryhory Skovoroda. In the latter, Western influence is much more pronounced. Skovoroda’s characteristic themes include individualism and a preference for land and nature over the city while his way of expression is close to folkloric. Despite an ambivalence and tension, Skovoroda does not build an opposition of the Russian and the Ukrainian; however, the recognizably Ukrainian cultural space which he creates differs considerably from that of the Russian Orthodoxy of the time.